PENINGKATAN PENGETAHUAN MELALUI KEGIATAN PENYULUHAN MARKISA (MARI KITA CEGAH ISPA) DI DESA MATA WAWATU KECAMATAN MORAMO UTARA TAHUN 2023 - Effendy, Devi Savitri; Saktiansyah, La Ode Ahmad; Suhadi, Suhadi; Nurmaladewi, Nurmaladewi (Universitas Halu Oleo, 2023)
The number of cases of communicable diseases that occur in the community such as Acute Respiratory Infection (ARI) which every year is included in the top 10 diseases that occur in the community of Watunggarandu Village. This infectious disease is mostly caused by the low level of community knowledge and unfavorable environmental health conditions and community behavior. The lack of knowledge of the Mata Wawatu Village community is one of the causes of the occurrence of infectious diseases in the community, as well as the high intensity of exposure to material transport vehicles. Service and empowerment activities in the form of outreach to the community are one of the solutions in reducing cases of infectious diseases. Extension activities are carried out using poster media, so that they can attract and increase the seriousness of the community in conducting counseling. Before and after the activity, pre and post tests were carried out regarding community knowledge about ISPA. After counseling, it was shown that the people in Mata Wawatu village experienced an increase in knowledge from previously they did not know about ISPA. With this increase in knowledge, the Mata Wawatu village community can prevent various things that trigger the cause of ARI.